Involvement of TGF-β and Autophagy Pathways in Pathogenesis of Diabetes: A Comprehensive Review on Biological and Pharmacological Insights - Heydarpour, Fatemeh; Sajadimajd, Soraya; Mirzarazi, Elahe; Haratipour, Pouya; Joshi, Tanuj; Farzaei, Mohammad Hosein; Khan, Haroon; Echeverría, Javier (Frontiers in Pharmacology, 2020)
Despite recent advancements in clinical drugs, diabetes treatment still needs further progress. As such, ongoing research has attempted to determine the precise molecular mechanisms of the disorder. Specifically, evidence supports that several signaling pathways play pivotal roles in the development of diabetes. However, the exact molecular mechanisms of diabetes still need to be explored. This study examines exciting new hallmarks for the strict involvement of autophagy and TGF-β signaling pathways in the pathogenesis of diabetes as well as the design of novel therapeutic strategies. Dysregulated autophagy in pancreatic β-cells due to hyperglycemia, oxidative stress, and inflammation is associated with diabetes, and accompanied by dysregulated autophagy in insulin target tissues and progression of diabetic complications. Consequently, several therapeutic agents such as adiponectin, ezetimibe, GABA tea, geniposide, liraglutide, guava extract, and vitamin D were shown to inhibit diabetes and its complications though modulation of autophagy pathway. Another pathway involving TGF-β, appears to contribute to the progression of diabetes, insulin resistance, and autoimmunity in both type 1 and 2 diabetes as well as complications in diabetes. Subsequently, drugs that target TGF-β signaling, especially naturally derived ones such as resveratrol, puerarin, curcumin, hesperidin, and silymarin as well as Propolis, Lycopus lucidus and Momordica charantia extracts, may become promising alternatives to current drugs in diabetes treatment. This review provides keen insights into novel therapeutic strategies for the treatment of diabetes.